2010
DOI: 10.1039/c002534h
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitors of c-Myc transcriptional factor suppress proliferation and induce apoptosis of promyelocytic leukemia cell via cell cycle arrest

Abstract: c-Myc plays a decisive role in the proliferation of HL-60 promyelocytic leukemia cells. In the present study, we demonstrated that an inhibitor of c-Myc/Max/DNA complex formation has a high potentiality as a suppressor of c-Myc-involved cell signaling. We prepared recombinant c-Myc and Max proteins encompassing the human-origin DNA binding and dimerization domains, and tested a chemical library of 6480 small molecules for their inhibitory effect on the in vitro formation of the c-Myc/Max/DNA complex as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…It has been previously reported that small-molecule inhibitors of c-myc suppress proliferation and induce apoptosis of promyelocytic leukemia cells via cell cycle arrest (39,40). Although our data show that 8-Cl-cAMP induced the downregulation of c-myc, the mechanism for this action is not well defined.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been previously reported that small-molecule inhibitors of c-myc suppress proliferation and induce apoptosis of promyelocytic leukemia cells via cell cycle arrest (39,40). Although our data show that 8-Cl-cAMP induced the downregulation of c-myc, the mechanism for this action is not well defined.…”
Section: Discussioncontrasting
confidence: 50%
“…To date, efforts to target c-Myc have identified only a small number of molecules with low biochemical potency and limited biological characterization (Bidwell et al, 2009; Hammoudeh et al, 2009; Jeong et al, 2010), underscoring both the challenge of targeting c-Myc as well as the enduring need for chemical probes of c-Myc transcriptional function. Considering chromatin as a platform for signal transduction (Schreiber and Bernstein, 2002), we have undertaken to inhibit Myc transcription and function through displacement of chromatin-bound, co-activator proteins using competitive small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with c-Myc described earlier, drugs that target disordered regions have shown promising initial results both in vitro and in vivo, and more metabolically stable analogues are currently in development [6,22,52]. An ability to modify the behaviour of disordered proteins via the use of small molecules may have profound implications for disease.…”
Section: Thermodynamics Of Protein-ligand Bindingmentioning
confidence: 92%